Design of an Off-Grid Hybrid Power Generation System for a Telecommunication Base-Transceiver Station: A Case Study of Cell Site at Oke-Imobi, Nigeria - Olabisi, Patrick; Ajayi, Olusola (Journal of Electronic Voltage and Application, 2025)
Hybrid of energy resources has proved to be an innovative means of providing off-grid power to infrastructures in remote locations where there is limited access to the national power supply grid. Adopting a mix of renewable energy resources with battery backup, and gas generator, to determine the optimum mix of the energy resources to meet particular load demands is a major challenge. Load profile for the case cell site was used as input to the simulation software, HOMER (evaluation version), to simulate the mix of energy resources to meet optimum power supply requirement. For cost effective power solution, the optimum period of 4–6 hours per day and a converter of 3 kW were used to obtain the following results for various mix: use of solar, wind and gas generator with 78.4 hours Autonomy produced 6,319 kWh/yr, in excess by 1694 kWh/yr (26.8%), Zero Unmet load and Capacity Shortage; use of solar and gas generator with 85.3 hours Autonomy produced 6,126 kWh/yr., in excess by 1526 kWh/yr (24.8%), with Zero Unmet load and Capacity Shortage; use of wind and gas generator with 177 hours Autonomy produced 5043 kWh/yr in excess by 198 kWh/yr (3.92%), Zero Unmet load and Zero Capacity Shortage; and, the use of solar and wind with 19.7 hours Autonomy produced 4,509 kWh/yr in excess by 632 kWh/yr, (14%), Unmet load of 621 kWh/yr and Capacity Shortage of 811 kWh/yr. Therefore, for the study area, the use of wind and gas generator produced the optimal supply of highest autonomy and minimal excess power with unmet load and zero capacity shortage.